Dispositional goal orientation and perceptions of coach motivational climate on attitudes towards doping among Kenyan endurance runners - Kevin Kiprotich Kipchumba; Elijah Rintaugu; Francis Mwangi; Benson Gathoni (PLoS ONE, 2025)
Changing athletes’ attitudes towards doping has been shown as crucial in prevention efforts in combating doping in sports, with dispositional goal orientation and perceptions of coach motivational climate identified as factors shaping doping attitudes among athletes. The purpose of this study was to examine the relationships between dispositional goal orientation and motivational climate on attitudes towards doping among Kenyan Endurance runners. A cross-sectional survey design was used to collect data from 323 Kenyan runners with 215 males (66.6%) and 108 females (33.3%). The study assessed athletes’ goal orientation through the Task and Ego Goal Orientation Sport Questionnaire, perceptions of coach motivational climate through Perceived Motivational Climate in Sport Questionnaire, and attitudes towards doping through Performance Enhancement Attitude Scale. Descriptive statistics, correlation analysis, Mann-Whitney U tests and Kruskal-Wallis H tests was used for data analysis. The study found significant inverse relationships between mastery climate and doping attitudes (rho = -.242; p <.001), as well as between task orientation and doping attitudes (rho = -.158; p <.004). Conversely, performance climate (rho =.362; p <.001) and ego orientation (rho =.362; p <.001) showed significant positive relationships with doping attitudes. There were no significant differences in doping attitudes based on age (U = 11582.500, p <.191), gender (U = 11437.500, p <.827) and athlete’s length of experience (χ2 (2) = 1.359, p <.507). The study concludes that fostering mastery-oriented coach motivational climate and promoting task-oriented goal orientation could effectively cultivate anti-doping attitudes among athletes and enhance clean sport.